2017
DOI: 10.7860/jcdr/2017/28720.10376
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Psychosocial Impact after One Year of Orthodontic Treatment Using PIDAQ Adapted for Indian Population

Abstract: Results showed significant improvement in the psychosocial impact of malocclusion with a reduction in the self-perceived needs of patients with orthodontic treatment. The psychometric instrument used may be recommended as an Oral Health Related Quality of Life (OHRQoL) assessment tool for the population in India for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
9
26
0
Order By: Relevance
“…The correlations between the changes in OHRQoL measured by PIDAQ and the IOTN-AC aesthetic changes, were higher and signi cant in comparison to the associations with CPQ11-14-ISF-16 ( Table 6). The ndings of the present study are consistent with the ndings of Garg et al 22 who found statistically signi cant associations (P < 0.001) between the PIDAQ changes and self-perceived IOTN-AC changes after treatment among their sample. Overall, the ndings direct research to employ more condition-speci c measures in evaluating patient-reported outcomes in orthodontic treatment, and they also support the perception that orthodontic treatment and improved dental aesthetics have a positive impact on individuals OHRQoL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The correlations between the changes in OHRQoL measured by PIDAQ and the IOTN-AC aesthetic changes, were higher and signi cant in comparison to the associations with CPQ11-14-ISF-16 ( Table 6). The ndings of the present study are consistent with the ndings of Garg et al 22 who found statistically signi cant associations (P < 0.001) between the PIDAQ changes and self-perceived IOTN-AC changes after treatment among their sample. Overall, the ndings direct research to employ more condition-speci c measures in evaluating patient-reported outcomes in orthodontic treatment, and they also support the perception that orthodontic treatment and improved dental aesthetics have a positive impact on individuals OHRQoL.…”
Section: Discussionsupporting
confidence: 92%
“…The "large" improvements in OHRQoL when PIDAQ was used as a measure, are similar to the results of a study conducted on 93 patients in India, where the authors reported "large" (Effect size = 1.47) signi cant (P < 0.001) reductions in mean PIDAQ scores after treatment. 22 When age was accounted for in relation to the mean change in PIDAQ total scores, a statistical signi cance (p = 0.04) was observed for two age groups (Adolescents 10-19 years and young adults 20-35 years); however, this was not found to be signi cant when gender differences (males and females) were considered (p = 0.31); nonetheless such ndings can only be con rmed with larger samples, that would help and be able to account for a variety of individual characteristics. 22 The discrepancy between examiner IOTN-AC assessments and self-perceived or lay IOTN-AC assessments for the need of orthodontic treatment has been reported in other studies, [22][23][24] and this was evident in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "large" improvements in OHRQoL when PIDAQ was used as a measure, are similar to the results of a study conducted on 93 patients in India, where the authors reported "large" (Effect size=1.47) significant (P<0.001) reductions in mean PIDAQ scores after treatment. 22 When age was accounted for in relation to the mean change in PIDAQ total scores, a statistical significance (p=0.04) was observed for two age groups (Adolescents 10-19 years and young adults 20-35 years); however, this was not found to be significant when gender differences (males and females) were considered (p=0.31); nonetheless such findings can only be confirmed with larger samples, that would help and be able to account for a variety of individual characteristics. 22 The discrepancy between examiner IOTN-AC assessments and self-perceived or lay IOTN-AC assessments for the need of orthodontic treatment has been reported in other studies, [22][23][24] and this was evident in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Malocclusion has been shown to be associated with psychosocial issues among adolescents. 5,6 Usually, these issues are evaluated through questionnaires on self-esteem and quality of life, such as the Rosenberg scale 7 and the Child Perceptions Questionnaire. 8 The Child Perceptions Questionnaire, for instance, was originally developed in Canada and was translated, cross-culturally adapted and validated in South American countries, including Brazil 9 and Peru.…”
Section: [ E P U B a H E A D O F P R I N T ]mentioning
confidence: 99%